Une théorie de l’Etat social - Bernard Billaudot (Revue de la Régulation)
This paper deals with the definition of the Welfare State. A renewed vision of the institutional basic pattern of modern society is proposed, in which the Welfare State is conceived as a more or less developed component of any modern State. The Welfare State was set in the main Western countries at the end of the XIXth Century in order to answer the social question. It is a specific form. As a consequence, the ecological question needs to broaden the concept of Welfare State. It is impossible to answer the ecological question if we stay stuck in the system of justification specific to Western modernity.